A Practical Guide to Frozen Section Technique - Peters, Stephen R. (Springer New York : Imprint: Springer, 2010)
A Practical Guide to Frozen Section Technique offers an easy to learn approach to frozen section technique in the form of a highly illustrated handbook intended for onsite use in the laboratory. The book begins with a novel, clearly delineated, step by step approach to learning continuous motion brush technique. Emphasis is placed on recognizing and correcting artifacts during the preparation process. The book addresses all of the steps in the preparation of slides from cutting through cover-slipping. The author's unique, original techniques for tissue embedding including face down embedding in steel well bars, frozen block cryoembedding and paper cryoembedding are detailed. Variables key to the quality of the preparation including block temperature, tissue properties and section thickness are detailed. The book also covers understanding the cryostat and basic maintenance and care.Sections covering techniques used in Mohs dermatologic surgery, and techniques used in basic animal and human research are discussed by noted experts in their field. A Practical Guide to Frozen Section Technique will be of great value to pathologists, pathology residents in training and also experimental pathology researchers that rely upon this methodology to perform tissue analysis in research.